Growth of carbon nanorodes on tungsten filaments of light bulbs - Thongtem S. (2014)
Carbon nanorodes (CNRsj were grown on the wavy surface of the filaments of light bulbs in 10 ml.s-1 Ar containing 0.1 and 0.2 ml.s-1 C2H2 at a temperature of 900 K. SEM and EDX analyses show locally selective growth of the nanorodes composing of carbon. Selected area electron diffraction (SAED) pattern shows that it is carbon atoms with hexagonal structure. TEM analysis shows the image of CNRs with uneven surface. In addition, electron emission of the CNRs grown on the filaments was measured using applied voltages up to 250 V and the results are in accord with the Fowler-Nordheim equation.